Forms of Involvement of Gifted Students in Research Work in the East Ukrainian Region (End of the 20th – Beginning of the 21st Century) - Maryna Kabanets (Pedagogical Discourse, 2019)
The article deals with the organization of research work of senior school students as a means of providing pedagogical provision for the gifted. The experience of educational establishments of the East Ukrainian region is shown on the example of the lyceum of Donetsk National University, Luhansk Oblast Junior Academy of Sciences, Dobropillia branch of the Junior Academy of Sciences, the history museum of Bakhmut of Donetsk oblast, and Mariupol city technological lyceum.The main tasks of the research work of gifted children have been defined. Factors influencing the research work of schoolchildren, the role of the scientific supervisor, and the work of the lyceum scientific society have been analysed. The role of regional branches of the Junior Academy of Sciences in pedagogical provision of the gifted has been considered, namely, their goals, organisational forms, and achievements. The key conditions influencing the efficiency of research work of gifted schoolchildren, typology of scientific supervisors have been highlighted; examples of the main organizational forms of involving senior high school students in research work have been given. They include: Junior Academy of Sciences of Ukraine, scientific societies and schools of young researchers, research projects as a part of lyceum curriculum, conferences, colloquiums, seminars, meetings with leading scholars, and participation in conducting joint research with students of higher educational institutions.The basics of students’ scientific research work have been developed by teachers and scientists of the first lyceums in Ukraine, which are based on the idea of the creative personality and understanding of the lyceum as a pedagogical system that is intended to train students for scientific and practical activity.Senior students’ research work stimulates interest, develops critical thinking and responsibility, develops confidence and communication skills, helps in their professional orientation, and provides creative self-realization.